Faktor-Faktor yang Berhubungan dengan Response time Tenaga Kesehatan di Ruang Instalasi Gawat Darurat (IGD) - Wahyu Surani; Ahmat Pujianto (LPPM UNIKAL, 2023)
The emergency room (IGD) is the main entrance for patients with emergency conditions. One indicator of the success of medical management of emergency patients is the speed of providing adequate help or response time. Fast response time will be achieved with support from factors, both internal factors (training, years of service, education) and external factors (availability of tools and medicines, and workload). This study aims to identify factors related to the response time of health workers in the Emergency Room of RSU Kota Tarakan. This study design was cross- sectional with a total sample of 38 health workers who served in the Emergency Room of RSU Tarakan. Data analysis used Kendall Tau analysis. The results of this study showed that there was a relationship between internal factors (training and length of service), external factors (availability of equipment and medicines) and the response time of health workers at Tarakan City Public Hospital (p-value <0.05). This research is expected to be a reference for the hospital to continue to involve officers in various training activities that can support the development of officer competence, and can ensure the availability of equipment and medicines that may be often needed by officers.Keywords:Emergency room, external and internal factor, response time